VIRTUAL LEARNING ENVIRONMENT AND LEARNING APPROACH AMONG PRE-CLINICAL UNDERGRADUATE MEDICAL STUDENTS DURING COVID-19 PANDEMIC - Fellicia Naurah Andryas; Agneta Irmarahayu; Nurfitri Bustamam (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: The ongoing COVID-19 pandemic has bestowed upon the global citizens what is now known as the new normal. The Ministry of Education and Culture of Indonesia has acted accordingly by commanding every academic institution to practice online learning to lower the transmission of the SARS-COV-2 virus. This abrupt pedagogical transformation imposes a new challenge for both students and teachers. Consequently, continuous monitoring and evaluation of the study process are essential to maintain high quality education. This research aimed to illustrate the perception of student's experienced virtual learning environment (VLE), chosen learning approach, and the association between them.Methods: A cross-sectional design was chosen for this study. Participants (n=210) currently registered as pre-clinical undergraduate medical students during the 2020/2021 academic year were asked to complete an online survey. Online Learning Environment Survey (OLES) and Revised Study Process Questionnaire 2 Factors (R-SPQ-2F) are used to determine VLE effectiveness and learning approach, respectively.Results: The study showed that 99% (n=208) of the students perceived their VLE as highly effective and 88,6% (n=186) used the deep learning approach. Fisher’s exact test revealed a significant correlation between perceived VLE and the learning approach (p=0,013). Conclusion: An effective VLE is of paramount importance as it influences students' approach to learning during their study. Academic institution needs to support proper evaluation of VLE to ensure high quality education is being delivered continuously.